The Effect of Wrongful Conviction Rate on Death Penalty Support and How It Closes the Racial Gap - Wu, Sishi (American journal of criminal justice, 2022)
Prior studies have revealed that wrongful conviction may affect people’s view of the death penalty. But few of them explained why people who believed innocent people were executed still supported the death penalty. This study proposes that what matters may not be whether respondents believed that wrongful convictions existed or not, but rather their beliefs about the frequency of it. It examines how different estimates of the rate of wrongful conviction, rather than general concerns of innocence, affect views about capital punishment. Using Gallup data in three years, I found that people’s perceived wrongful conviction rates were negatively associated with support for the death penalty. The mediation analyses show that perceived wrongful conviction rate fully mediated the effect of being Black on death penalty support in all three years of observation. This research indicates quantifying the risk of wrongful convictions plays an important role in understanding people’s death penalty support.